Perancangan Sistem Absensi Otomatis Mahasiswa Berbasis RFID Terintegrasi Google Spreadsheet dan Smart Door Lock - Nadia Putri Pardani; Bekti Yulianti (JURNAL TEKNOLOGI INDUSTRI, 2026)
Attendance systems play an important role in academic management as they relate to discipline and the validity of student presence. However, manual attendance methods remain vulnerable to fraud, such as proxy attendance, and are not integrated with physical room access control. This study designs and evaluates an RFID RC522-based attendance system integrated with a smart door lock using ESP32 within a cloud-based IoT architecture. Experimental testing was conducted on lecturer and student cards using parameters including success rate, False Accept Rate (FAR), False Rejection Rate (FRR), and system response time. The system implements a cloud-based whitelist mechanism through Google Spreadsheet and infrared sensor verification to validate physical access. The results show a 100% success rate in UID reading and data logging with a FAR of 0%. The FRR reached 33.33% for lecturer cards and 6.67% for student cards, while the response time ranged from 7–10 seconds due to cloud communication latency. The integration improves attendance accuracy and room access security, although response time and system stability still require optimization..